Miracle in the cave : the 12 lost boys, their coach, and the heroes who rescued them - Cochrane, Liam (HarperOne, an imprint of HarperCollinsPublishers, 2019)
For nine days twelve young soccer players and their coach were confined in the dark by rising waters in the caverns of Tham Luang in Chang Rai, Thailand. With no food or drinking water except the condensation found on the cave walls, their survival seemed unlikely. Yet against the odds, a team of determined divers traversed monsoon floodwaters and narrow passageways to find Coach Ek, a stateless orphan devoted to Buddhism, and his young players alive and hopeful. Liam Cochrane spent more than two weeks on the scene, and was stationed outside of the cave entrance in daily contact with divers and other key members of the rescue team, reporting the story for the Australian Broadcasting Corporation. In this mesmerizing and inspiring book, he recounts this ultimate race-against-the-clock event. Filled with never-before-reported details based on exclusive access to the boys, their families, and the rescue team, Miracle in the Cave chronicles the Wild Boars' ordeal in the cave, and the plan that unfolded outside--including the contentious political negotiations, the early misadventure that halted the operation for crucial hours, and the death of Thai Navy SEAL diver Saman Kunan. Going deep inside the area between the Thai and Myanmar border, better known for methamphetamines and illegal wildlife trade, Cochrane guides us through every aspect of the adventure-turned-nightmare-turned miracle: the team's agonizing wait in the darkness; the rescuers' battle against the forces of nature; the work of international experts who pooled their skills to help. Chochrane evokes the rollercoaster of emotions every step of the way--the terror, optimism, sadness, and joy of this indelible experience. Filled with a spirit of true grit, Miracle in the Cave is a courageous tale of perseverance and a celebration of an inspiring moment when the world came together in hope.--